PUTUSAN TINDAK PIDANA NARKOTIKA TERHADAP ANAK OLEH HAKIM PADA PUTUSAN NOMOR: 5/PID.SUS-ANAK/2020/PN PDP - Rifka Zuwanda; Rangga Prayitno (Ekasakti Jurnal Penelitian dan Pengabdian, 2022)
A criminal conspiracy to commit a crime of narcotics abuse as an intermediary in buying and selling narcotics carried out by children is charged by the public prosecutor with Article 114 paragraph (1) with a sentence of life imprisonment or a minimum prison sentence of 5 years and a maximum prison sentence of 20 years. In a case that occurred in the jurisdiction of the Padang Panjang District Court, a child with the initials MB together with Witness Farhan Dwi Ghani carried out an attempt or an evil conspiracy to commit a criminal act of narcotics and narcotics precursors, without rights or against the law as intended in Article 127 paragraph ( 1) letter a of Law Number 35 of 2009 concerning Narcotics which in plant form weighs more than 1 Kilogram or more than 5 marijuana trees.